Case report Melanosis of prostate – Benghazi, Libya - M. K., Farid, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
We present the case number 22 of prostatic melanosis in the literature reports. Prostatic melanosis is a very rare, benign lesion characterized by the presence of melanin both in the epithelium of the prostate gland as well as in the stromal dendritic cells, requiring no additional treatment. It constitutes the melanocytic lesions of the prostate together with blue nevus and melanoma.